2023
DOI: 10.1111/dsji.12286
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between supply chain management practice and curriculum: A location analytics exercise

Abstract: This teaching brief explores how and why location analytics should be taught in business schools using three objectives. First, an explanation is provided for the importance of including location analytics in the standard business school curriculum—especially in the field of supply chain management. Second, a lack of GIS‐based location analytics methods in business school curricula is demonstrated. Third, a three‐part location analytics exercise is introduced to contribute to the supply chain management curric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…For instance, Geographic Information Systems (GIS), which is crucial to location analytics and became vital for supply chains during COVID-19, is seldom covered in business schools. Ritchie et al (2023) sampled business schools and textbooks and found that less than 2% of business schools sampled offered a GIS-based analytics course and only three of 12 textbooks sampled mentioned GIS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Geographic Information Systems (GIS), which is crucial to location analytics and became vital for supply chains during COVID-19, is seldom covered in business schools. Ritchie et al (2023) sampled business schools and textbooks and found that less than 2% of business schools sampled offered a GIS-based analytics course and only three of 12 textbooks sampled mentioned GIS.…”
Section: Introductionmentioning
confidence: 99%
“…Ritchie et al. (2023) sampled business schools and textbooks and found that less than 2% of business schools sampled offered a GIS‐based analytics course and only three of 12 textbooks sampled mentioned GIS.…”
Section: Introductionmentioning
confidence: 99%